IMPLEMENTASI PROGRAM HUNIAN TERJANGKAU MILIK (HTM) DI WILAYAH JAKARTA TIMUR - Muhamad Zhidane Furiyansyah; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The fulfillment of adequate housing needs remains a social issue in urban areas, particularly for low-income communities. The Government of DKI Jakarta Province, through the Affordable Homeownership Program (Hunian Terjangkau Milik/HTM), seeks to expand access to homeownership by providing more affordable financing schemes. In its implementation, various challenges continue to affect the course of the program. This study aims to analyze the implementation of the Affordable Homeownership Program in East Jakarta and to identify factors influencing its implementation. The research employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation studies involving the Office of Public Housing and Settlement Areas, the Housing Fund Management Unit, as well as program beneficiaries and prospective beneficiaries. Data analysis was conducted qualitatively by referring to the policy accuracy theory proposed by Riant Nugroho and the policy implementation theory of Van Meter and Van Horn. The findings indicate that the Affordable Homeownership Program in East Jakarta has generally been implemented in accordance with prevailing regulations; however, its implementation has not yet been fully optimal, particularly in terms of target accuracy, environmental appropriateness, and process accuracy. Factors supporting program implementation include resources, the characteristics of implementing agencies, and the attitudes of implementers, while inhibiting factors include policy standards and objectives, and social, economic, and political environmental conditions. This study is expected to serve as an evaluative reference for local governments in improving the effectiveness of sustainable housing programs.